Carbon Finance How Carbon and Stock Markets are affected by Energy Prices and Emissions Regulations - Veld-Merkoulova, Yulia; Viteva, Svetlana (Springer International Publishing : Imprint: Springer, 2016)
Maximizing reader insights into the methodologies and cutting-edge research concerning the financial aspects of carbon markets, this book analyzes the economic and financial effects of carbon trading and regulations on the stock market prices of individual companies as well as the joint effects of regulations and of the prices of oil and gas on the prices and volatility of the traded carbon securities.  Focussing on the European Union Emissions Trading Scheme (EU ETS), which is the most developed carbon trading scheme worldwide, the results obtained for the EU ETS are used as a benchmark for the new carbon markets being developed in North America and worldwide. After reading this book, the reader will: • Learn how the European market for carbon emission allowances work; • Be aware of the institutional development of the market and of the regulatory environment of the EU Emissions Trading Scheme; • Get acquainted with the regression methodologies used to evaluate the impact of regulatory and other events on energy and financial markets; • Become familiar with the recent research results on the links between carbon market regulations, energy prices and the returns and volatility of carbon-linked financial instruments and stock market prices; • Get informed about the possibilities of carbon emissions regulations and their impact on financial markets.  This book will be instrumental for the market regulators, researchers and advanced students interested in energy finance, and for the finance practitioners and investors in the energy and carbon intensive industries.